Kingdom of the Netherlands-Netherlands : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
The Netherlands showed strong growth and employment performance owing to its fiscal consolidation and structural reforms. Executive Directors commended the sound macroeconomic and structural policies, which have raised potential output, kept inflation low, and promoted strong employment growth. They underscored the need for prudent fiscal policy, and welcomed the budget balance, support for trade liberalization, and the soundness of the financial system. They emphasized the need to address labor market weaknesses, and improve product market performance to sustain economic growth.